C. Wright Mills and the Ending of Violence - Brewer, J. author. aut Link
XI, 197 p.
Keywords: This book has two aims: to clarify the meaning of C. Wright Mills's depiction of the sociological imagination; and to use this to develop a sociological framework that assists in understanding the process by which communal violence has ended in Northern Ireland and South Africa. The contrast between these two societies is a familiar one, but the book is novel by developing an explanatory framework based on Mills's 'sociological imagination'. This model merges developments in the two countries at the individual, social structural and political arenas in order to account for the emergence of their peace processes.